Collaboration, virtual co-creation, and value-added logistics: an empirical study of competitiveness in indonesian logistics clusters - Dodi Permadi; Vanessa Gaffar; Lili Adi Wibowo; Alfira Sofia (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study empirically examines the causal relationships among Emerging Markets Logistics (EML), Dynamic Logistics Cluster Capabilities (DLCC), Logistics Collaboration Strategy (LCS), Virtual Co-Creation Innovation Program (VCCIP), Value Added Logistics Implementation (VALI), and Logistics Competitiveness Performance (LCP) within logistics clusters in Indonesia. Using a cross-sectional, non-experimental survey design, data were collected from 188 logistics firms operating at the organizational level and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with a hierarchical component approach. Measurement reliability, convergent and discriminant validity, and structural model adequacy were all confirmed. The results show that EML and DLCC have positive and significant direct effects on LCP, while LCS strengthens the impact of market dynamics on competitiveness. However, collaboration alone does not directly generate virtual innovation. VCCIP plays a critical mediating role by transforming dynamic cluster capabilities into value-added logistics services, which in turn significantly enhance competitiveness. The findings reveal two distinct causal pathways: an efficiency-driven pathway through collaboration and an innovation-driven value creation pathway through virtual co-creation and value-added logistics. These results contribute empirically to dynamic capability theory by clarifying the mechanisms through which cluster-based capabilities and virtual co-creation jointly drive logistics competitiveness in an emerging market context.